A comparison of students enrolled in academic and general programs on attitude toward school, attitude toward self, participation in extra-curricular activities and ratings of students by teachers - Coish, E. Calvin, 1948- (1973)
Thesis (M.Ed.)--Memorial University of Newfoundland, 1973. Education Bibliography: leaves 98-104.